Densimetry for the Quantification of Sorption Phenomena on Nonporous Media Near the Dew Point of Fluid Mixtures - Markus Richter (Nature Portfolio, 2017)
Abstract Phase equilibria of fluid mixtures are important in numerous industrial applications and are, thus, a major focus of thermophysical property research. Improved data, particularly along the dew line, are needed to improve model predictions. Here we present experimental results utilizing highly accurate densimetry to quantify the effects of sorption and capillary condensation, which exert a distorting influence on measured properties near the dew line. We investigate the (pressure, density, temperature, composition) behaviour of binary (CH4 + C3H8) and (Ar + CO2) mixtures over the temperature range from (248.15 to 273.15) K starting at low pressures and increasing in pressure towards the dew point along isotherms. Three distinct regions are observed: (1) minor sorption effects in micropores at low pressures; (2) capillary condensation followed by wetting in macro-scale surface scratches beginning approximately 2% below the dew-point pressure; (3) bulk condensation. We hypothesize that the true dew point lies within the second region.